Encouraging student entrepreneurial activities in online business: evidence from of UiTM Kedah / Law Kuan Kheng ...[ et al.] - Law, Kuan Kheng; Khamis, Muhammad Sazri; Ishak, Wan Irham (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Recently, more fresh graduates are showing interest to participate in entrepreneurship activities. One of the benefits of the involvement of fresh graduates in entrepreneurship is it can help the government to overcome the problems of unemployment among graduates. One of the p opular entrepreneurship activities among the young businesspeople is online business where they do it as part time or full time work. The reason is because online business is considered as one of the easiest ways for someone particularly young graduates to start up their own business. Online business requires less capital and business transactions are conducted virtually. There is no face to-- face communication between the seller and buyer. All processes and transactions are conducted via social media such a s Facebook, Instagram, twitter, WhatsApp, messenger and etc. The aim of this paper is to highlight the initiatives taken by public universities to support government’s effort to encourage university students to participate in entrepreneurial activities